EFFECT OF FERTILIZER ON SUNFLOWER PRODUCTIVITY AND SEED QUALITY - Hanhur, V.; Kosminskyi, О.; Len, O.; Totskyi, V. (Scientific Progress & Innovations, 2022)
Traditionally, the most common oil crop in Ukraine is sunflower (Helianthus annuus L.). Sunflower belongs to the group of agricultural crops that require a background of mineral nutrition. The purpose of the research was to find out the effect of mineral fertilizers and foliar top dressing with a biopreparation on yield and quality indicators of sunflower seeds. Based on the results of the research, it was established that on average for 2017–2019, the maximum seed yield of 3.02 t/ha was formed by the medium-ripe hybrid Kamenyar against the background of N32Р32K32 application + foliar feeding of plants with biological preparations Organic Balance 0.5 l/ha + Liposam 0.5 l/ha). At a similar level of fertilization, the Polit 2 and Pochatok hybrids formed a lower seed yield, respectively by 0.06–0.28 t/ha or 2.4–10.0 %, compared to the Kamenyar hybrid. It was found that the Polyt 2, Pochatok and Kamenyar hybrids were the most productive when applied with mineral fertilizers in the dose of N32Р32K32 plus foliar feeding of plants with biological preparations Organic Balance 0.5 l/ha + Liposam 0.5 l/ha. The level of seed yield was, respectively, 2.81; 2.94; 3.02 t/ha, which is 0.44; 0.45; 0.47 t/ha more than the control. On the same fertilizer option, the oil content in the seeds of sunflower hybrids was the maximum (in the hybrid Polit 2 – 55.7 %, Pochatok – 53.6 %, Kamenyar – 54.5 %) and the weight of 1000 seeds (in the hybrid Polit 2 – 49.8 g, Beginning – 47.7 g, Kamenyar – 39.8 g). It was investigated that the introduction of mineral fertilizers in the dose of N32Р32K32 also contributed to an increase in seed yield compared to plots without fertilizers, respectively by 12.2; 13.3; 8.6 %. But at the same time, the productivity of hybrids was inferior to the best version of fertilizer by 4.1–8.3 %. Only the feeding of plants with biological preparations Organic Balance 0.5 l/ha + Liposam 0.5 l/ha was effective. The yield increase, compared to the control, was equal to 0.16–0.26 t/ha.